New antitumour agents with α, β-unsaturated δ-lactone scaffold: Synthesis and antiproliferative activity of (−)-cleistenolide and analogues. Issue 14 (15th July 2016) - Benedeković, Goran; Kovačević, Ivana; Popsavin, Mirjana; Francuz, Jovana; Kojić, Vesna; Bogdanović, Gordana; Popsavin, Velimir
Graphical abstract: Abstract: A stereoselective total synthesis of (−)-cleistenolide (1 ) fromd -glucose has been achieved. This new approach for the synthesis of (−)-cleistenolide and analogues involves a one- C -atom degradation of the chiral precursor, ( Z )-selective Wittig olefination, followed by the final δ-lactonisation. Synthesized compounds showed potent growth inhibitory effects against selected human tumour cell lines, especially 2, 4, 6-trichlorobenzoyl derivative12, which in the culture of MDA-MB 231 cells displayed the highest activity (IC50 0.02 μM) of all compounds under evaluation. A preliminary SAR study reveals the structural features that are beneficial for antiproliferative activity of synthesized δ-lactones, such as presence of either electron-withdrawing or electron-donating substituents in the aromatic ring, as well as the presence of cinnamoyl functionality instead of benzoyl group at the O-7 position.